2014
DOI: 10.1111/trf.12676
|View full text |Cite
|
Sign up to set email alerts
|

A prenatal prediction model for total nucleated cell count increases the efficacy of umbilical cord blood banking

Abstract: Our prenatal prediction model increases the efficacy of obtaining informed consent for UCB banking while still allowing relevant numbers of CBUs to be banked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 25 publications
3
20
0
9
Order By: Relevance
“…In India, the present study is the first to characterize both CD34+ and CD90+ cell content in cord blood with respect to some of the major neonatal parameters. Significant impact of birth weight on HSC content of the cord blood has been reported by other studies [15][16][17], which is found to be supportive to the present observation. Results of multivariable analysis showed that with the unit rise in birth weight there was an increment of 0.761% of CD34+ and 0.799% of CD90+ cell counts.…”
Section: Discussionsupporting
confidence: 95%
“…In India, the present study is the first to characterize both CD34+ and CD90+ cell content in cord blood with respect to some of the major neonatal parameters. Significant impact of birth weight on HSC content of the cord blood has been reported by other studies [15][16][17], which is found to be supportive to the present observation. Results of multivariable analysis showed that with the unit rise in birth weight there was an increment of 0.761% of CD34+ and 0.799% of CD90+ cell counts.…”
Section: Discussionsupporting
confidence: 95%
“…Por otro lado, se encontró, que de las variables neonatales, la longitud del cordón fue la única que se correlacionó con el recuento total de células nucleadas y no hubo ninguna otra correlación entre las demás variables maternas o neonatales analizadas como vía del parto, peso materno, edad gestacional, peso de placenta, peso del bebé datos que contrastan en cuanto a que el peso del neonato al momento del nacimiento es el principal factor neonatal que afecta el Numero de CD34+ y Recuento de células nucleadas (7)(8)(9)(10)22,(26)(27)(28)(29)(30)(31). Llama la atención el hecho que se hubiera encontrado correlación solamente entre la longitud del cordón umbilical y el recuento total de células nucleadas y no también con el recuento de células CD34+, teniendo en cuenta, y según los resultados del presente estudio, la existencia de correlación entre estos dos marcadores de calidad, inquietudes que valen la pena tener en cuenta para próximas investigaciones.…”
Section: Discussionunclassified
“…At different gestational ages, the volumes of UCBs obtained and the proportions of UCB‐SCs are different. Higher gestational ages are related to larger volumes of UCB and greater total nucleated cell (TNC) counts, whereas lower gestational ages are associated with greater numbers of hematopoietic stem cells and greater numbers of colony‐forming units (CFUs) of UCBCs (Manegoldbrauer et al, ). In preterm UCB, there are fewer nucleated cell counts, probably due in part to decreased placental weight and size.…”
Section: Sources Of Ucb‐scs In Preterm Infantsmentioning
confidence: 99%
“…The quality and quantity of UCB‐SCs can be influenced by many kinds of perinatal factors. Studies have shown that maternal body mass index is positively correlated with TNC counts (Alsweedan, Musalam, & Obeidat, ; Manegoldbrauer et al, ). However, parity is negatively correlated with CFUs and TNC counts (Manegoldbrauer et al, ), and there is a 17% decrease in hematopoietic stem cell counts with every additional birth (Ballen et al, ).…”
Section: Sources Of Ucb‐scs In Preterm Infantsmentioning
confidence: 99%
See 1 more Smart Citation